Why Do Cities Innovate in Public Health? Implications of Scale and Structure - Paul A. Diller (Washington University Law Review, 2014)
Big cities have frequently enacted public health regulations—especially with respect to tobacco use and obesity—that go beyond the state and federal regulatory floors. That cities innovate in public health at all is remarkable. They have less to gain financially from more stringent regulation than higher levels of government, which shoulder more of the burden of Medicare and Medicaid. Cities are supposed to fear mobile capital flight; if they regulate, businesses will leave. Moreover, because innovation is costly and likely to be copied by others when successful, a free-rider problem might inhibit local policy innovation generally. Cities’ prolific regulation in the public health sphere in spite of countervailing predictions thus demands an explanation. This Article aims to offer one, focusing on what makes local lawmaking unique from lawmaking at the federal and state levels. This Article argues that cities’ smaller scale, concentrated political preferences, and streamlined lawmaking processes facilitate public health innovation. With respect to structure in particular, cities’ unicameral legislatures and lack of a supermajority requirement allow affirmative regulatory legislation to proceed more expeditiously. Cities thus stand in contrast to the currently dysfunctional federal government, in which vested interest groups can more easily block regulatory legislation they dislike. In highlighting what is different about the local lawmaking process, this Article aims to better inform the debate about the extent of local power, which plays out in doctrinal areas like home rule and preemption.
Keywords: health; public health; tobacco use; obesity; local power